Neuroinflammatory Processes, A1 Astrocyte Activation and Protein Aggregation in the Retina of Alzheimer’s Disease Patients, Possible Biomarkers for Early Diagnosis - Grimaldi, Alfonso; Pediconi, Natalia; Oieni, Francesca; Pizzarelli, Rocco; Rosito, Maria; Giubettini, Maria; Santini, Tiziana; Limatola, Cristina; Ruocco, Giancarlo; Ragozzino, Davide; Di Angelantonio, Silvia (Frontiers in Neuroscience, 2019)
Alzheimer’s disease (AD), a primary cause of dementia in the aging population, is characterized by extracellular amyloid-beta peptides aggregation, intracellular deposits of hyperphosphorylated tau, neurodegeneration and glial activation in the brain. It is commonly thought that the lack of early diagnostic criteria is among the main causes of pharmacological therapy and clinical trials failure therefore, the actual challenge is to define new biomarkers and non-invasive technologies to measure neuropathological changes in vivo at pre-symptomatic stages. Recent evidences obtained from human samples and mouse models indicate the possibility to detect protein aggregates and other pathological features in the retina, paving the road for non-invasive rapid detection of AD biomarkers. Here, we report the presence of amyloid beta plaques, tau tangles, neurodegeneration and detrimental astrocyte and microglia activation according to a disease associated microglia phenotype (DAM). Thus, we propose the human retina as a useful site for the detection of cellular and molecular changes associated with Alzheimer’s disease.